Enzymatic noncovalent synthesis of peptide assemblies generates multimolecular crowding in cells for biomedical applications. Issue 96 (24th November 2021) - Yi, Meihui; Tan, Weiyi; Guo, Jiaqi; Xu, Bing
Abstract : This article highlights the unique features of enzymatic noncovalent synthesis (ENS) for generating multimolecular crowding in cells and the relevant applications for biomedicines. Abstract : Enzymatic noncovalent synthesis enables the spatiotemporal control of multimolecular crowding in cells, thus offering a unique opportunity for modulating cellular functions. This article introduces some representative enzymes and molecular building blocks for generating peptide assemblies as multimolecular crowding in cells, highlights the relevant biomedical applications, such as anticancer therapy, molecular imaging, trafficking proteins, genetic engineering, artificial intracellular filaments, cell morphogenesis, and antibacterial, and briefly discusses the promises of ENS as a multistep molecular process in biology and medicine.